2008
DOI: 10.4314/thrb.v10i1.14340
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and usability of district health information software: case studies from Tanzania

Abstract: Abstract:The District Health Information System (DHIS) software from the Health Information System Programme (HISP) based in South Africa is widely implemented in many developing countries as a health data analysis tool. Through the HISP Tanzania project, the DHIS was piloted in five districts in Tanzania. The objective of this study was to qualify and quantify the extent to which district health workers consider the adaptation of the DHIS software to the needs of the routine health management information syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…However, there has not been enough and continuous training on how to fully use the software to allow proper flow of information for successful implementation and provision of screening services. A study conducted in Tanzania revealed that most users complained that one week trainings were not enough for them as users to become familiar with the software (Lungo, ). A study on how to achieve and maintain high‐quality performance of health workers in low‐resource settings concluded that one of the factors leading to ineffective implementation of various health interventions in the health sector is poor dissemination of information (Rowe, De Savigny, Lanata, & Victora, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there has not been enough and continuous training on how to fully use the software to allow proper flow of information for successful implementation and provision of screening services. A study conducted in Tanzania revealed that most users complained that one week trainings were not enough for them as users to become familiar with the software (Lungo, ). A study on how to achieve and maintain high‐quality performance of health workers in low‐resource settings concluded that one of the factors leading to ineffective implementation of various health interventions in the health sector is poor dissemination of information (Rowe, De Savigny, Lanata, & Victora, ).…”
Section: Discussionmentioning
confidence: 99%
“…A study in India examined the architectural constraints that constituted a common problem across various HIS in the country at both national and state levels . Another study on reliability and usability of the District Health Information Software 2 in Tanzania recommended improvements in the user interface to reduce human errors in data entry . To assess viability, utilization, and effectiveness of a district HMIS, it was important to in‐build pre‐implementation, concurrent, and post‐implementation evaluation criteria .…”
Section: Resultsmentioning
confidence: 99%
“…29 Another study on reliability and usability of the District Health Information Software 2 in Tanzania recommended improvements in the user interface to reduce human errors in data entry. 34 To assess viability, utilization, and effectiveness of a district HMIS, it was important to in-build pre-implementation, concurrent, and post-implementation evaluation criteria. 35 These evaluation criteria would foster contextual design, an adaptive system, and alignment with user expectations.…”
Section: System Design Barriersmentioning
confidence: 99%
“…Therefore, the WHO has continued advising its member countries to ensure that they have properly functioning HMIS since having the accurately collected, analyzed and stored data could allow informed and rational policy decisions in the health sector to be made [1]. Thus, a proper planning for IPTp services is impossible in the absence of reliable sources of routine health service data mostly collected from HFs, and this is true for the general service data [1,2,28-30] and data for specific interventions like IPTp [18]. …”
Section: Introductionmentioning
confidence: 99%